Resistência de união de diferentes zircônias envelhecidas - Gallina, Bernardo Luiz (2017)
Zirconia has been extensively researched due to its biocompatibility, mechanical resistance and having an aesthetic property, being widely used in dentistry. Prettau Anterior zirconia presents superior esthetics for anterior region, when compared to other zirconia. The objective of this study was to evaluate the bond strength of two Zirconias with different compositions.For this purpose, twenty-two (22) blocks were made and cut with 3x5x10mm of each of the evaluated materials: Zirconia ICE Zirkon Translucent (ZT) and ZirconiaPrettau Anterior (ZPA). The specimens were made using resin cement RelyX Unicem U200 with a vinylpolysiloxane matrix assistence. Then, 11 blocks of each group were separated in two storage times: 1 and 90 days of storage in distilled water at 37 ° C, totaling n = 11. The Micro-shearing test was performed at a speed of 0.5 mm / min on the Universal testing machine. The samples were also submitted to fracture analysis and analysis by scanning electron microscopy. The results were submitted to the Shapiro Wilk test, Analysis of Variance ANOVA (two-way) and then to Tukey's test, p <0.01. The means obtained for the group aged in 1 day were: 7.56 (+1.02) for ZT, 9.38 (+1.22) for ZPA. And for the samples that aged 90 days were: 0.47 (+1.02) for ZT, 1.74 (+0.58) for ZPA. Statistically significant differences were observed for the factors: ceramic type and aging time. According to the obtained results, it was possible to observe that Zirconia Prettau Anterior showed results statistically superior to Zirconia ICE Zirkon Translucent, in both aging times evaluated.